EFEKTIFITAS PERBEDAAN KONSUMSI BLACK GARLIC TUNGGAL DAN MAJEMUK TERHADAP PENURUNAN TEKANAN DARAH PASIEN HIPERTENSI : EFEKTIFITAS PERBEDAAN KONSUMSI BLACK GARLIC TUNGGAL DAN MAJEMUK TERHADAP PENURUNAN TEKANAN DARAH PASIEN HIPERTENSI - ika cahyaningrum; Errick Endra Cita (STIKes Maharani Malang, 2023)
One of the management of hypertension is complementary therapy using natural ingredients. Black garlic is a complementary therapy made from natural ingredients by processing fermented garlic. The purpose of this study was to analyze the effectiveness of differences in the consumption of single and double black garlic in reducing blood pressure in hypertensive patients, using a quasi-experimental research method with a non-randomized pre-test post-test control group design. There were 2 groups in the study, namely the group of respondents who were given single black garlic therapy (group 1) and the group of respondents who were given compound black garlic therapy (group 2). The research was conducted from April to June 2022 in Sumber Gesing Kulon Gedangan, Malang Regency. The population in this study were hypertension sufferers in Sumber Gesing Kulon Gedangan Hamlet. The sampling technique used consecutive sampling with a total sample of 40 samples. Data analysis used the independent t test with the result that there were differences in systolic and diastolic blood pressure between the black garlic treatment for the single onion variant and the compound shallot variant with a ρ value for systolic blood pressure 0.001 < 0.05, and a ρ value for diastolic blood pressure 0.003 < 0. 05.